Cabaran Pengajaran Digital Secara Maya Dan Kesediaan Murid Pasca Covid 19 - Nik Md. Saiful Azizi Nik Abdullah; Rohani Ali; Nurul Nadiah Yahya; Rabi'atul Athirah Muhammad Isa; Muhammad Isa (USIM Press, 2024)
Vol. 6 No. 2 (2021): Jurnal Sains Insani